PERSEPSI CIVITAS AKADEMIKA TENTANG LGBT DALAM TINJAUAN HUKUM ISLAM DAN HAK ASASI MANUSIA SERTA UPAYA DALAM MENANGKAL PERTUMBUHANNYA DI LINGKUNGAN KAMPUS - Novianti, Linda; Rahmadika, Sarah; Rahayu, Wati (Family Law Study Program, Faculty of Sharia and Law, UIN Sunan Gunung Djati Bandung, 2024)
AbstractThis research aims to determine the perception of the academic community towards LGBT in the campus environment, LGBT from the perspective of Islamic Law and Human Rights, as well as efforts to prevent the growth of LGBT in the campus environment. The method used in this research is qualitative, with data collection techniques through interviews and literature studies from relevant books, laws and articles. The research results show a diversity of views among the academic community towards LGBT. These diverse perceptions affect social relations in the campus environment and create challenges in achieving inclusivity. As for Islamic law, same-sex relationships are considered to violate religious norms based on the interpretation of the verses of the Koran and al-Hadith. Meanwhile, from a human rights perspective in Indonesia, LGBT people have their human rights protected, including the right to health, as regulated in Article 25 of the UDHR. However, it should be noted that protecting the human rights of LGBT people is not always related to the recognition or legalization of sexual orientations that are considered deviant. This perspective is reflected in Law of the Republic of Indonesia Number 1 of 1974 concerning Marriage. Then, efforts to prevent the growth of LGBT in the campus environment can be carried out through seminars, campaigns regarding the impact of LGBT, as well as building collaboration with NGOs to formulate firm policies regarding the negative impact of LGBT.